Hubungan Kejenuhan Belajar dalam Jaringan dengan Prokrastinasi Akademik - Rozzaqyah, Fadhlina (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
This study aims to obtain an overview of the relationship between learning saturation and academic procrastination of students of the Guidance and Counseling Study Program, Sriwijaya University. The sampling technique used was totaling sampling on 81 4th semester students in the Guidance and Counseling study program at Sriwijaya University. The research method uses a correlational study approach and data collection uses a learning saturation scale and academic procrastination scale collected through google form. Dataanalysis was carried out using the Pearson Product Moment formula in the SPSS 21 application. The results showed the correlation value rxy = 0.719, which means that learning saturation in the network has a strong positive relationship with student academic procrastination, where the higher academic procrastination, the higher academic procrastination.